Ellery C. Stowell papers - Stowell, Ellery C. (Ellery Cory), 1875-1958.
Correspondence, diaries, writings, reports, sermons, notebooks, family papers, printed matter, scrapbooks, photographs, and other papers pertaining chiefly to Stowell's career as a professor of international law at American University (Washington, D.C.), Columbia University, and George Washington University; years as a student at Harvard University and universities in Berlin, Germany, and Paris, France; and travels in America, Asia, and Europe. Subjects include armament limitation; the International Naval Conference, London, England, 1908-1909; the International Peace Conference, Hague, Netherlands, 1907; World War I; and World War II. Other subjects include academic freedom, the Hall of Nations program at American University, and Stowell's activities with civic organizations including the Better Government League (Washington, D.C.) and the Patriotic Service League (New York, N.Y.). Includes papers of the Stowell (Stovall), Fuller, and Tapley families.
Library of Congress Prints and Photographs Division.
Author, jurist, and professor of international law.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fuller family; Stovall family; Tapley family; American University (Washington, D.C.) -- Faculty; American University (Washington, D.C.). -- Hall of Nations; Better Government League (Washington, D.C.); Columbia University -- Faculty; George Washington University -- Faculty; Harvard University -- Students; Patriotic Service League (New York, N.Y.); Academic freedom; Disarmament; International law; International law -- Study and teaching; Peace -- Congresses; Political participation -- United States; Universities and colleges -- France -- Paris; Universities and colleges -- Germany -- Berlin; World War, 1914-1918.; World War, 1939-1945.; America -- Description and travel; Asia -- Description and travel; Europe -- Description and travel; Authors; Educators; Jurists